Trends in Use of Midodrine in the ICU: A Single-Center Retrospective Case Series. Issue 7 (July 2018) - Rizvi, Mahrukh S.; Trivedi, Vrinda; Nasim, Faria; Lin, Erica; Kashyap, Rahul; Andrijasevic, Nicole; Gajic, Ognjen
Abstract : Objectives: Midodrine is an oral alpha-agonist approved for orthostatic hypotension. The use of midodrine as a vasopressor sparing agent has steadily increased in the ICU despite limited evidence for its safety in that setting. We describe the trends in use and reported side effects and complications of midodrine in multidisciplinary ICUs of a tertiary care institution. Design: Single-center retrospective case series. Setting: Medical and surgical ICU patients from January 2011 to October 2016 at Mayo Clinic, Rochester. Patients: Adult patients admitted to any ICU who received midodrine for hypotension were eligible. Interventions: None. Measurements and Main Results: We reviewed the mean arterial pressures and cumulative vasopressor dose before and after midodrine administration and assessed for reported complications. During the study period, a total of 1, 119 patients were initiated on midodrine, 56% in surgical ICUs, 42% in medical ICUs, and 2% in a mixed medical and surgical neurology ICU. There was a significant decrease in the number of patients on vasopressors 24 hours after initiation of midodrine (663 to 344; p < 0.001); among the patients that remained on vasopressors, there was a significant decrease in the median cumulative vasopressor dose ( p = 0.002). There was a significant increase in median mean arterial pressure 24 hours after initiation of midodrine among patients who were not on vasopressors (65–68; p < 0.01). Asymptomatic bradycardia (heart rate < 50 beats/min) was the most common side effect ( n = 172 patients, median 39 beats/min). Two patients developed bowel ischemia after initiation of midodrine that prompted discontinuation of midodrine in one case. Evaluating trends of utilization, the off-label use of midodrine has increased steadily over the years across ICUs. Conclusions: Our results suggest that midodrine is being increasingly used as an adjunct to increase mean arterial pressure and facilitate weaning of vasopressors in the ICU. Prospective trials are required to further establish the appropriate timing, efficacy, safety, and cost-effectiveness of midodrine use in ICU patients. Abstract : Supplemental Digital Content is available in the text.